2015
DOI: 10.1177/2324709615590198
|View full text |Cite
|
Sign up to set email alerts
|

Unusually Located Stroke After Chemotherapy in Testicular Germ Cell Tumors

Abstract: Testicular cancer is a type of malignancy that affects young adults and has high rates of cure; however, as any malignancy, it is associated with an increased risk of ischemic or hemorrhagic cerebrovascular disease, given the systemic tumor effects or side effects of chemotherapy, which in turn increases morbidity, functional impairment, and additional risk of early death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Interestingly, Fung et al recently observed increased CVD mortality only during the first year of follow‐up (based on only 6 cardiac deaths and 5 cerebrovascular disease deaths), although the median follow‐up was only 6.5 years after chemotherapy in their study. Some case reports have described severe acute myocardial infarction or stroke shortly after chemotherapy in TC survivors, although these events are rare and usually not fatal. Differences in the underlying CVD risk factors, lifestyles, and prophylactic use of low‐molecular‐weight heparin to prevent platinum‐associated thromboembolic events may underlie these heterogeneous findings with respect to CVD mortality …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Fung et al recently observed increased CVD mortality only during the first year of follow‐up (based on only 6 cardiac deaths and 5 cerebrovascular disease deaths), although the median follow‐up was only 6.5 years after chemotherapy in their study. Some case reports have described severe acute myocardial infarction or stroke shortly after chemotherapy in TC survivors, although these events are rare and usually not fatal. Differences in the underlying CVD risk factors, lifestyles, and prophylactic use of low‐molecular‐weight heparin to prevent platinum‐associated thromboembolic events may underlie these heterogeneous findings with respect to CVD mortality …”
Section: Discussionmentioning
confidence: 99%